Changes in Toothbrushing Behavior and Knowledge through Dental Health Care Education and Experience for Elementary School Students (Medico Legal Update, 2019)
Background/Objectives: To form habits through the dental health education for assisting with mid tolong-term oral health maintenance of elementary school students, surveys were conducted from March toDecember of 2018.Method/Statistical Analysis: The data was encoded then statistically analyzed using SPSS ver. 23.0, and thelevel of significance was set as 0.05. Cross-tabulation was conducted for the grade distribution depending onthe gender, and the frequency analysis was conducted for the existence of oral health recognition, school’soral health education behaviors and changes in toothbrushingbehaviors after the oral health education.Findings: As for dental health education, 74.8% students responded that it is ‘helpful’ for dental healthcare, and 71.7% students responded that it is ‘helpful’ for dental health education usage and method. As fordental health recognition, ‘healthy’ was the most frequent response, and 49.2% students responded they haveexperienced ‘bleeding from the gum’ when toothbrushing. As for the toothbrushing related questions, 35.5%respondents were using rotational method, and 54.1% responded that they brush after lunch. “between 2 to3 minutes” was the most popular with 33.1%. As for the distribution of correct answers for dental healthknowledge before and after education, the correct answers which asked ‘if the cause of gum disease is dentalplaque’ increased after education(89.9%) compared to before (76.1%). The question which asked ‘if oneshould brush teeth before going to sleep’, the correct answer was higher after education(98.4%) comparedto before (89.6%). The question which asked ‘if fruits, milk and vegetables assist with tooth cleanliness’, thecorrect answer was higher after education(88.2%) compared to before(79.4%).Improvements/Applications: Consequentially, forming proper habits through repeated education and